Structural characterization of starches from Chinese jackfruit seeds (Artocarpus heterophyllus Lam). (July 2018) - Zhang, Yanjun; Zhang, Yutong; Xu, Fei; Li, Shize; Tan, Lehe
Abstract: To investigate its molecular structure, starch was extracted from five jackfruit cultivars (M1, M5, M6, M11, and BD) and separated into amylose and amylopectin. The values for weight-average molar mass (Mw) and average radius of gyration (Rg) of the jackfruit starches (1.74 × 10 7 g/mol - 4.61 × 10 7 g/mol, 115.4 nm - 144.2 nm) were similar to those of rice and potato starch, higher than those of maize and waxy rice starches, but lower than those of barley starches. The jackfruit starches exhibited higher proportions of A and B1 chains, lower proportions of B2 and B3 + chains and shorter average chain lengths (38.33%–33.89%, 39.06%–39.58%, 17.13%–18.43%, 4.96%–8.62% and 18.27–19.71, respectively). Compared with the other cultivars, starch from the BD cultivar exhibited the lowest Mw and Rg of amylose (1.42 × 10 6 g/mol and 55.3 nm) and the highest Mw and Rg of amylopectin (6.99 × 10 7 g/mol and 132.8 nm). The amylose of the M1 cultivar and the amylopectin of the BD cultivar showed more compact structures than did the other starches identified. It was found that with increasing amylose content, the Mw and Rg of amylose and the proportions of B2 and B3 + chains showed an increased trend, whereas the Mw and Rg of amylopectin and proportions of A and B1 chains displayed the opposite trend. This study provides the theoretical basis for further research of starch structures. Graphical abstract: Image Highlights: The molecular weight and fine structure were studied from five jackfruit cultivars. The Mw of jackfruit starch was similar to rice starch, higher than maize starch. The jackfruit starches exhibited the higher proportions of A and B1 chains. The amylose of M1 and amylopectin of BD species showed compact structure than others. The amylose Mw and proportions of B2 and B3+ chains increased with amylose content.